2018
DOI: 10.1093/tas/txy124
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Communication: A comparison of cardiac lesions and heart weights from market pigs that did and did not die during transport to one Ontario abattoir1

Abstract: In-transit losses of market hogs represent a small proportion of all market-weight pigs shipped in a year. This suggests that individual pig factors may be a significant cause of in-transit losses along with more traditionally considered environmental and transport factors. An investigation was performed to determine whether cardiac pathology and heart weights were associated with pigs that did or did not die during transport to an abattoir. The hearts from 70 pigs that died in-transit to one Ontario abattoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
(20 reference statements)
2
5
0
Order By: Relevance
“…Our necropsy results showed that the LV mass/THW ratio was 0.62. Similar findings were published by Zurbrigg et al 23 : LV mass/THW ratios ranged from 0.62 to 0.66 in 396 hearts from slaughtered pigs.…”
Section: Predicting Heart Size For Xenotransplantation Experimentssupporting
confidence: 90%
“…Our necropsy results showed that the LV mass/THW ratio was 0.62. Similar findings were published by Zurbrigg et al 23 : LV mass/THW ratios ranged from 0.62 to 0.66 in 396 hearts from slaughtered pigs.…”
Section: Predicting Heart Size For Xenotransplantation Experimentssupporting
confidence: 90%
“…It should also be mentioned that the outer heart volume could e.g. potentially be influenced by hypertrophy of ventricular walls and dilatation of ventricular chambers, which is reported to be common in finisher pigs in Canada 6 . Whether such lesions exist among purebred nucleus pigs, is questionable, but compensatory remodelling could potentially give a deviating relationship between heart and body size.…”
Section: Discussionmentioning
confidence: 99%
“…quantifying the capacity of the heart and lungs. Previous studies 2 , 6 show that heart lesions and abnormalities, like hypertrophy of the ventricular walls are quite common in finishers and growing pigs, even in animals that seem healthy 6 . More specifically, van Essen et al 2 observed that some traits describing the circulatory capacity, like cardiac output and stroke volume in pigs did not scale proportionally with body weight (BW) according to the allometric scaling laws.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations